Struggle For Public Welfare In An Enemy Of The People Drama (1882) By Henrik Ibsen: A Sociological Approach. - Pambudi, Nurcahyani Retno; , Drs. M. Thoyibi, M. S.; , Titis Setyabudi, S.S. M. Hum (2013)
The research is proposed to analyze the social problem in An Enemy of the People drama. The major problem in this article is to explain how the social problem reflected in An Enemy of the People drama. The object of the study is An Enemy of the People drama written by Henrik Ibsen. Qualitative study is a method which is used to analyze the sociological problem reflected in the drama. The result of this study is Henrik Ibsen shows the social reality of Norway. Although Norway in late nineteenth century was developing country, Henrik Ibsen also criticized the society for ignoring the bad impact of the development public and physical environment.